2018
DOI: 10.1007/s00259-018-4160-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved specificity with 68Ga PSMA PET/CT to detect clinically significant lesions “invisible” on multiparametric MRI of the prostate: a single institution comparative analysis with radical prostatectomy histology

Abstract: Ga-PSMA PET/CT may better reflect RP histopathology compared to mpMRI when considering multifocal and bilateral disease. These findings may influence surgical planning, targeted biopsy and focal therapy strategies and require further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 42 publications
3
89
0
3
Order By: Relevance
“…Intraprostatic tumor localization has been investigated in some recent studies . In one study, gross tumor volume detection of mp‐MRI and Ga‐68 PSMA PET/CT were compared with histopathology and both of the modalities showed high sensitivity and specificity in detection of primary PCa .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraprostatic tumor localization has been investigated in some recent studies . In one study, gross tumor volume detection of mp‐MRI and Ga‐68 PSMA PET/CT were compared with histopathology and both of the modalities showed high sensitivity and specificity in detection of primary PCa .…”
Section: Discussionmentioning
confidence: 99%
“…PI‐RADS (Prostate Imaging—Reporting And Data System) scores were determined according to the second version, PI‐RADS v2 of the American College of Radiology (ACR) . PI‐RADS 4 and 5 scans were considered a likely result, PI‐RADS 3 was considered equivocal and PI‐RADS 2 result was defined as an unlikely result . Extraprostatic extension (EPE) of the tumor, invasion of seminal vesicle (SVI) and bladder neck invasion (BNI) were also reported visually as positive or negative.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another retrospective study revealed 58 patients who underwent MRI with 68 Ga-PSMA PET/CT followed by radical prostatectomy. 68 Ga-PSMA PET/CT correctly detected more foci (78%, AUC 0.817) than mpMRI (69%, AUC 0.729) [22]. 68 Ga-PSMA PET/CT may better reflect the histopathology of radical prostatectomy compared to mpMRI when considering multifocal and bilateral disease.…”
Section: Diagnostic Performance Of 68 Ga-psma Petmentioning
confidence: 97%
“…Studies generally show PSMA-PET has improved sensitivity for detecting intraprostatic cancer lesions over MRI (74-92% vs. 53-73%). [9][10][11][12][13] Most studies are retrospective by design and report improved detection for PSMA-PET over mpMRI for both primary and secondary prostate cancer lesions. 9,12,14 Also, most studies have focused on high-risk prostate cancer with few intermediate risk cancers (grade group ≤3) being studied.…”
Section: Introductionmentioning
confidence: 99%